Efecto del extracto acuoso de semillas de salvia hispánica l. sobre diabetes inducida en mus musculus balb/c”. - Vaca Meza, Eveleny Tirsa (2016)
The purpose of this research was to determine the effect of aqueous extract of Salvia hispanica L. seed on induced diabetes in Mus musculus BALB / c. It were 18 males Mus musculus Balb / c, weighing between 25 to 30 g, which were randomized into 3 groups, with 6 animals each. The control group consists of 6 Mus musculus Balb / c with induced diabetes, received physiological saline for 21 days. Grup problem I and II was consisted of 6 Mus musculus Balb / c with diabetes induced each, received 2 ml of aqueous extract of the seeds of Salvia hispánica L. (chia) v.o at 1% and 2% for 14 days, respectively. The grups problem received physiological saline for the last 7 days of the experiment as post-treatment. Basal glucose was determined at the start of the experiment and after 48 hours after administration of alloxan that receiving a single dose (75 mg / kg / day alloxane in citrate buffer - intraperitoneal route) and also at 1, 3, 7, 14 and 21 days in all study groups. Glucometer Accu-Chek Active was use a small incision in the apex of the tail for obtain a homogeneous drop, on the test strip of the glucometer. In the results of the phytochemical march, both the 1% and 2% aqueous extract have flavonoids, tannins, alkaloids and sesquiterpenlactones present. It was concluded that the aqueous extracts of Salvia hispanica L. have hypoglycemic effect, being the greater effect in the extract of 2%.